Assessing Outcomes: Practical Methods and Evidence. Issue 2 (July 2014) - Moore, Jon; Owen, Jesse
<x xml:space="preserve">Abstract</x> University counseling center clients' (N = 52) perceptions of precounseling functioning were highly correlated with their actual well‐being scores at intake. The magnitude of change based on perceptions of precounseling functioning to current well‐being was approximately double of what is found from the difference of actual precounseling well‐being to current well‐being scores. Retrospective methods for assessing precounseling functioning are best suited for comparison among clients or counseling processes.